2020
DOI: 10.1186/s13007-020-00659-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive identification of single hard seed via multispectral imaging analysis in six legume species

Abstract: Background: Physical dormancy (hard seed) occurs in most species of Leguminosae family and has great consequences not only for ecological adaptation but also for agricultural practice of these species. A rapid, nondestructive and on-site screening method to detect hard seed within species is fundamental important for maintaining seed vigor and germplasm storage as well as understanding seed adaptation to various environment. In this study, the potential of multispectral imaging with object-wise multivariate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…Multispectral imaging technology integrates conventional imaging and spectroscopy information simultaneously, and is non-destructive, simple, rapid, and does not have the requirement of sample pre-treatment [ 9 , 10 ]. These merits make it suitable for seed purity testing and seed contamination determination.…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral imaging technology integrates conventional imaging and spectroscopy information simultaneously, and is non-destructive, simple, rapid, and does not have the requirement of sample pre-treatment [ 9 , 10 ]. These merits make it suitable for seed purity testing and seed contamination determination.…”
Section: Introductionmentioning
confidence: 99%
“…The multispectral imaging data was recorded in MSI VideometerLab4 (Videometer A/S, Herlev, Denmark), which contains 19 monochrome light-emitting diodes (LEDs) with non-uniform wavelength distribution, i.e., 375, 405, 430, 450, 470, 505, 525, 570, 590, 630, 645, 660, 700, 780, 850, 870, 890, 910, 940 and 970 nm. The LEDs flash continuously in a scan time of five seconds and produce a monochrome image at each wavelength [ 31 , 32 ]. Before the spectral information was collected, the 100 seeds in the five aging groups were numbered as 1~100, and each petri dish with 25 seeds was placed into the instrument for signal recording.…”
Section: Methodsmentioning
confidence: 99%
“…The 70% of the seeds in each sample harvest year were randomly selected as the training set and the other 30% were used for model testing. The classification performance of the model was evaluated by accuracy, sensitivity and specificity [ 31 ], with formula as followed. …”
Section: Methodsmentioning
confidence: 99%
“…Hu et al [54] examined seeds of six species within the Fabaceae family with MSI for the detection of hard seeds. For each species, 400 seeds were examined 70:30 in training and testing set, respectively, and following image acquisition seeds were imbibed for germination.…”
Section: Vigormentioning
confidence: 99%
“…In all three species studied, hard seeds showed a higher reflectance compared to non-hard seeds. Hu et al [54] used SVM analysis and found that wavelengths in the NIR-region, i.e., 970 nm (water) and 940 nm (lipids, were of highest importance in the separation of the two groups. However, for each species only one seed lot was represented in the analysis and there were proportionally fewer non-hard seeds which made the two groups unbalanced.…”
Section: Vigormentioning
confidence: 99%